Overview of pharmacodynamical research of traditional Chinese medicine on hyperuricemic nephropathy: from the perspective of dual-regulatory effect on the intestines and kidneys - Wang, Ting; Li, Li; Liu, Li; Tan, Ruirong; Wu, Qinxuan; Zhu, Xin; Hua, Hua; Dai, Ying; Li, Huan; Mao, Jiuzhou; Zhao, Junning; Yin, Zhujun (Frontiers in Pharmacology, 2025)
Uncontrolled hyperuricemia contributes to chronic kidney disease, characterized by renal inflammatory cell infiltration and tubulointerstitial fibrosis, eventually leading to renal failure. In addition to liver and kidney, the intestine tract plays a vital role in the development and progression of hyperuricemia and hyperuricemic nephropathy (HN) through various mechanisms. The conventional therapeutic strategy for HN is uric acid-lowering therapy (ULT) and renal protection; however, unsatisfactory results are often obtained in clinical practice. Growing evidence has demonstrated that traditional Chinese medicines (TCMs) achieve an anti-HN effect by modulating multiple targets and approaches with fewer side effects. Therefore, this paper reviews the pathogenesis of HN, including the role of soluble and insoluble urates in kidney and intestine, and the role of intestinal tract in the progression of HN. Meanwhile, the recent advancements in TCMs for the treatment of HN are summarized and analyzed, with a focus on their modulation of intestinal flora and metabolites, urate-related transporters, immuno-inflammation and barrier function in the intestines. Notably, for the first time, we propose the perspective that TCMs treat HN through a dual-regulatory effect on the intestines and kidneys. Additionally, the problems existing in current research and the feasible research strategies combined with emerging technologies such as fermentation and nanotechnology are discussed, thus providing novel ideas for HN management.